Dari Sakralitas Alam ke Etika Ekologis: Integrasi Ekoteologi Islam dan Pasang ri Kajang Melalui Konsep Eko-Nirvana - Rusli, Muh. Irfan; Wulandari, Andi Ulfa; Takbir, Muhammad (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
This study aimed to examine the integration of Islamic ecotheological values and Pasang ri Kajang as a solution to the ecological crisis in the contemporary era, particularly in the context of Makassar City, which had experienced deforestation, environmental pollution, and clean water scarcity. This study employed a qualitative approach through literature review and descriptive-critical analysis of Islamic sources and the local wisdom of the Ammatoa Kajang indigenous community. The results showed that Islamic ecotheology, based on the concepts of khalifah, mizan, fasad, and israf, had substantial compatibility with the values of Pasang ri Kajang, especially the principle of kamase-masea, which emphasized simplicity and harmony with nature. The integration of these values produced an ecological ethical paradigm that combined spiritual dimensions and local wisdom in viewing nature as a trust that must be preserved. The findings formulated the concept of Eko-Nirvana as a solution model that emphasized ecological spirituality, self-restraint in the use of natural resources, and collective moral responsibility for environmental sustainability. This study concluded that the integration of Islamic ecotheology and Pasang ri Kajang was effective as an alternative approach in fostering sustainable ecological awareness amid the modern environmental crisis.